1963
DOI: 10.1037/h0043297
|View full text |Cite
|
Sign up to set email alerts
|

Effect of goal box similarity on the after-effect of nonreinforcement and resistance to extinction.

Abstract: 4 groups of rats were trained to traverse a straight alley, 3 under the same pattern of partial reinforcement, 1 under consistent reinforcement. The partial groups were given intertrial reinforcement (ITR) following nonreinforced trials preceding reinforced trials. ITR consists in placing 5 by hand in the baited goal box during the intertrial interval. It was found, as hypothesized, that as similarity between the training goal box and the ITR goal box decreased, resistance to extinction increased. It was concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

1964
1964
1990
1990

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 9 publications
4
19
0
Order By: Relevance
“…The slower running in extinction in Group ITR than in Group Event-N agrees with the results of previous experiments (e.g., Capaldi & Spivey, 1963) that have shown that ITRs experienced prior to R trials that follow N trials decrease resistance to extinction. According to our analysis, this effect ofITRs occurs because event-generated SR occasioned by the ITR replaces event-generated SN as the operative memory on trials on which subjects would otherwise have learned to respond to SN.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The slower running in extinction in Group ITR than in Group Event-N agrees with the results of previous experiments (e.g., Capaldi & Spivey, 1963) that have shown that ITRs experienced prior to R trials that follow N trials decrease resistance to extinction. According to our analysis, this effect ofITRs occurs because event-generated SR occasioned by the ITR replaces event-generated SN as the operative memory on trials on which subjects would otherwise have learned to respond to SN.…”
Section: Discussionsupporting
confidence: 82%
“…Th~decreased resistance to extinction in Group Signal-R, relative to Group Event-N, obtained in Experiments 1 and 2 is strongly reminiscent of the decreased resistance to extinction produced by intertrial reinforcements (lTRs) scheduled to follow N trials that precede R trials (e.g., Capaldi & Spivey, 1963). In terms of the present analysis, ITRs occasion event-generated SR which then replaces event-generated SNas the operative memory.…”
Section: Methods Subjectsmentioning
confidence: 96%
“…The present spaced-trial results are consistent with 182 those of massed-trial ITR studies (Capaldi et al,196~;Capaldi & Spivey, 1963) and suggest that the partial reinforcement effect under 24-hr. intervals (e. g., Weinstock, 1954) is due to aftereffects remaining functional for 24 hr.…”
Section: Dhl('ussionsupporting
confidence: 82%
“…intervals (e. g., Weinstock, 1954) is due to aftereffects remaining functional for 24 hr. This conclusion assumes (Capaldi & Spivey, 1963) that ITR replaced the aftereffect of nonreinforcement with that of reinforcement most extensively in Group PB, less extensively in Group PW, and least extensively or not at all in Group PR, since ITR occurred following reinforced trials. Experiment II, which replicated and extended Experiment I, demonstrated that the partial reinforcement effect (Group C vs. Group PRJ can occur following a very small number of spaced trials, a result previously demonstrated with massed trials (Capaldi & Hart, 1962).…”
Section: Dhl('ussionmentioning
confidence: 99%
“…The effects of replacing aftereffects stimuli have been investigated, particularly in relation to experimental extinction, in studies which employed intertrial goalbox placements. For example, rewarded or nonrewarded goalbox placements interpolated between instrumental training trials reliably influence the size of the partial reinforcement extinction effect (Capaldi, Hart, & Stanley, 1963;Capaldi & Spivey, 1963, 1964Homzie, Rudy, & Carter, 1970;Spence, Platt, & Matsumoto, 1965).…”
mentioning
confidence: 99%